Exercise-Induced Neuroprotection of the Nigrostriatal Dopamine System in Parkinson's Disease - Hou, Lijuan; Chen, Wei; Liu, Xiaoli; Qiao, Decai; Zhou, Fu-Ming (Frontiers in Aging Neuroscience, 2017)
Epidemiological studies indicate that physical activity and exercise may reduce the risk of developing Parkinson's disease (PD) while clinical observations suggest that physical exercise can reduce the motor symptoms and cognitive impairments in PD patients. In experimental animals, a profound observation is that exercise of appropriate timing, duration and intensity can reduce dopamine (DA) toxin-induced lesion of the nigrostriatal DA system in animal PD models, although negative results have also been reported, potentially due to inappropriate timing and intensity of the exercise regimen. Exercise may also minimize DA denervation-induced medium spiny neuron (MSN) dendritic atrophy and other abnormalities such as enlarged corticostriatal synapse and abnormal MSN excitability and spiking activity. Taken together, epidemiological studies, clinical observations and animal research indicate that appropriately dosed physical activity and exercise may not only reduce the risk of developing PD in vulnerable populations but also benefit PD patients by potentially protecting the residual DA neurons or directly restoring the dysfunctional cortico-basal ganglia circuit, potentially via exercise-triggered production of endogenous neuroprotective molecules such as neurotrophic factors. Thus, exercise is a universally available, side effect-free medicine that should be prescribed to vulnerable populations as a preventive measure and to PD patients as a component of treatment. Future research needs to establish standardized exercise protocols that can reliably induce DA neuron protection, enabling the delineation of the underlying cellular and molecular mechanisms that in turn can maximize exercise-induced neuroprotection and neurorestoration in animal PD models and eventually in PD patients.